The geography of snake reproductive mode: a global analysis of the evolution of snake viviparity - Anat, Feldman; Aaron M., Bauer; Fernando, Castro-Herrera; Laurent, Chirio; Indraneil, Das; Tiffany M., Doan; Erez, Maza; Danny, Meirte; Cristiano de, Campos Nogueira; Zoltán, Tamás Nagy; Omar, Torres-Carvajal; Peter, Uetz; et al. (John Wiley & Sons, Ltd., 2015)
Aim :